Pengaruh Komite Audit, Ukuran Perusahaan dan Profitabilitas terhadap Earnings Management di Perusahaan Manufaktur Sektor Barang Konsumsi - Damayanti, Clarissa Aulia; Ulupui, I Gusti Ketut Agung; Perdana, Petrolis Nusa (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This study aims to examine the effect of the audit committee, firm size, and profitability on earnings management. Earnings management is proxied by discretionary accruals, audit committee is proxied by the number of audit committee members, firm size is measured by the natural logarithm of the firm's total assets, and profitability is measured by return on assets (ROA). The research method used is a quantitative method with secondary data. The analysis technique used is multiple linear regression analysis. The sample selection technique uses a purposive sampling method which consists of 41 manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for 2018-2021. The results of the study partially show that the audit committee has a positive and significant effect on earnings management, firm size has no significant effect on earnings management, and profitability has a positive and significant effect on earnings management. In addition, the audit committee, firm size, and profitability simultaneously have a significant effect on earnings management.